A Loading Micafungin Dose in Critically Ill Patients Undergoing Continuous Venovenous Hemofiltration or Continuous Venovenous Hemodiafiltration: A Population Pharmacokinetic Analysis. Issue 6 (December 2021) - Garbez, Nicolas; Mbatchi, Litaty C.; Maseda, Emilio; Luque, Sonia; Grau, Santiago; Wallis, Steven C.; Muller, Laurent; Lipman, Jeffrey; Roberts, Jason A.; Lefrant, Jean-Yves; Roger, Claire
Abstract : Background: In this study, the authors aimed to compare the pharmacokinetics (PK) of micafungin in critically ill patients receiving continuous venovenous hemofiltration (CVVH, 30 mL·kg −1 ·h −1 ) with those of patients receiving equidoses of hemodiafiltration (CVVHDF, 15 mL·kg −1 ·h −1 + 15 mL·kg −1 ·h −1 ) and determine the optimal dosing regimen using the developed model. Methods: Patients with septic shock undergoing continuous renal replacement therapy and receiving a conventional dose of 100 mg micafungin once daily were eligible for inclusion. Total micafungin plasma concentrations from 8 CVVH sessions and 8 CVVHDF sessions were subjected to a population PK analysis using Pmetrics. Validation of the model performance was reinforced by external validation. Monte Carlo simulations were performed considering the total ratio of free drug area under the curve (AUC) over 24 hours to the minimum inhibitory concentration (MIC) (AUC0-24 /MIC) in plasma. Results: The median total body weight (min–max) was 94.8 (66–138) kg. Micafungin concentrations were best described by a 2-compartmental PK model. No covariates, including continuous renal replacement therapy modality (CVVH or CVVHDF), were retained in the final model. The mean parameter estimates (SD) were 0.96 (0.32) L/h for clearance and 14.8 (5.3) L for the central compartment volume. External validation confirmed the performance of the developed PK model. Dosing simulations did not support the use of standard 100 mg daily dosing, except for Candida albicans on the second day of therapy. A loading dose of 150 mg followed by 100 mg daily reached the probability of target attainment for all C. albicans and C. glabrata, but not for C. krusei and C. parapsilosis . Conclusions: No difference was observed in micafungin PK between equidoses of CVVH and CVVHDF. A loading dose of 150 mg is required to achieve the PK/PD target for less susceptible Candida species from the first day of therapy. Abstract : Supplemental Digital Content is Available in the Text.